Superconducting properties in heavily overdoped Ba(Fe0.86Co0.14)2As2 single crystals - Kim, Jeehoon (2015)
We report the intrinsic superconducting parameters in a heavily overdoped Ba(Fe1-xCox)2As2 (x=0.14) single crystal and their influence in the resulting vortex dynamics. We find a bulk superconducting critical temperature of 9.8 K, magnetic penetration depth λab (0)=660 ± 50 nm, coherence length ξab (0)=6.4 ± 0.2 nm, and the upper critical field anisotropy γT→Tc ≈ 3.7. The vortex phase diagram, in comparison with the optimally doped compound, presents a narrow collective creep regime. The intrinsic pinning energy plays an important role in the resulting vortex dynamics as compared with similar pinning landscape and comparable intrinsic thermal fluctuations.